A survey of design features and provisions in suraus at petrol stations in Klang Valley - Md. Sharif, Harlina; Abdul Rashid, Khairuddin; Othman, Jamilah; Ahmad Sarkawi, Azila (Masjid Al-Azhar, Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2016)
Suraus at petrol stations along the highways in Klang Valley have facilitated Muslims in performing their obligatory prayers (salat) especially during the peak hours while commuting home from their workplace. Given that a surau is a simpler form of a masjid, whereby the later denotes a much more elaborate treatment to the facilitation of salat requirements, the surau has generally been accepted to provide the most basic and essential features (dharuriyat) for a Muslim prayer place. Although etymologically the word masjid only indicates the utility or place for performing salat and not the provision of a specific structure, the development of the mosque design from the time of the Prophet s.a.w. to our time today indicates that there are supplementary elements of design features that have become desirable provisions in enhancing user experience and the quality of salat. By conducting a visual survey on 13 suraus at petrol stations using non-randomised convenient sampling as an adopted methodology, this study documents three essential aspects of the surau: 1) design features, 2) supporting facilities, and 3) accessories provisions. The findings of the survey indicate the need for minimum standard requirements for design provisions of suraus at petrol stations.